PENDAMPINGAN KESEHATAN FISIK DAN MENTAL IBU HAMIL DAN MENYUSUI DI SOTH STANDART 2 BKB HARAPAN KITA 2 DALAM UPAYA PENCEGAHAN KEJADIAN STUNTING DI DESA SUMBEREJO KEC.BATU KOTA BATU - qotimah, qotimah; Sayuti, Sayuti; Setyowati, Susana (Penerbit Widina, Widina Media Utama, 2024)
The main purpose of this community service is to educate SOTH women so as to increase knowledge and understanding of the importance of maternal mental and physical health during pregnancy and breastfeeding. The main purpose of this community service is to educate SOTH women so as to increase knowledge and understanding of the importance of maternal mental and physical health during pregnancy and breastfeeding. To reduce the occurrence of stunting, female students are believed to improve the health of pregnant and lactating women by increasing their understanding of the topic, this in turn will result in healthier mothers, babies, and children The method used in this activity is by means of mentoring where before the activity and after the activity a post test is carried out to determine the increase in the understanding of SOTH students. This activity was attended by twenty mothers, including pregnant and lactating women, participating in SOTH in Batu City which took place in Sumberejo Village, Batu District, Batu City. With the hope that pregnant and lactating women can better understand their health, it is important to provide education about the mental and physical health of pregnant and lactating women;ABSTRAKTujuan utama Pengabdian masyarakat ini adalah untuk mendidik perempuan SOTH sehingga mampu meningkatkan pengetahuan dan pemahaman tentang pentingnya kesehatan mental dan fisik ibu selama kehamilan dan menyusui. Untuk mengurangi terjadinya stunting, siswi diyakini akan meningkatkan kesehatan ibu hamil dan menyusui dengan meningkatkan pemahaman mereka terhadap topik tersebut, hal ini pada gilirannya akan menghasilkan ibu, bayi, dan anak yang lebih sehat. Metode yang digunakan dalam kegiatan ini dengan cara pendampingan dimana sebelum kegiatan dan sesudah kegiatan dilakukan post test untuk mengetahui peningkatan pemahaman siswi SOTH. Kegiatan ini dihadiri Dua puluh orang ibu, termasuk ibu hamil dan menyusui, mengikuti SOTH di Kota Batu yang berlangsung di Desa Sumberejo, Kecamatan Batu, Kota Batu. Dengan harapan ibu hamil dan menyusui dapat lebih memahami kesehatan dirinya, maka penting untuk memberikan edukasi mengenai kesehatan mental dan fisik ibu hamil dan menyusui.